Responding to Typhoon Haiyan in the Philippines - McPherson, Michelle; Counahan, Megan; Hall, Julie Lyn (Western Pacific Surveillance and Response, 2015)
An editorial introducing this Supplementary Issue about the response to Typhoon Haiyan in the Philippines